Hyperoside Attenuate Inflammation in HT22 Cells via Upregulating SIRT1 to Activities Wnt/β-Catenin and Sonic Hedgehog Pathways - Jin Huang; Liang Zhou; Jilin Chen; Tingbao Chen; Bo Lei; Niandong Zheng; Xiaoqiang Wan; Jianguo Xu; Tinghua Wang (Neural Plasticity)
Neuroinflammation plays important roles in the pathogenesis and progression of altered neurodevelopment, sensorineural hearing loss, and certain neurodegenerative diseases. Hyperoside (quercetin-3-O-β-D-galactoside) is an active compound isolated from Hypericum plants. In this study, we investigate the protective effect of hyperoside on neuroinflammation and its possible molecular mechanism. Lipopolysaccharide (LPS) and hyperoside were used to treat HT22 cells. The cell viability was measured by MTT assay. The cell apoptosis rate was measured by flow cytometry assay. The mRNA expression levels of interleukin-1β (IL-1β), interleukin-6 (IL-6), interleukin-8 (IL-8), and tumor necrosis factor-α (TNF-α) were determined by quantitative reverse transcription polymerase chain reaction. The levels of oxidative stress indices superoxide dismutase (SOD), reactive oxygen species (ROS), catalase (CAT), glutathione (GSH), and malondialdehyde (MDA) were measured by the kits. The expression of neurotrophic factor and the relationship among hyperoside, silent mating type information regulation 2 homolog-1 (SIRT1) and Wnt/β-catenin, and sonic hedgehog was examined by western blotting. In the LPS-induced HT22 cells, hyperoside promotes cell survival; alleviates the level of IL-1β, IL-6, IL-8, TNF-α, ROS, MDA, Bax, and caspase-3; and increases the expression of CAT, SOD, GSH, Bcl-2, BDNF, TrkB, and NGF. In addition, hyperoside upregulated the expression of SIRT1. Further mechanistic investigation showed that hyperoside alleviated LPS-induced inflammation, oxidative stress, and apoptosis by upregulating SIRT1 to activate Wnt/β-catenin and sonic hedgehog pathways. Taken together, our data suggested that hyperoside acts as a protector in neuroinflammation.